2010
DOI: 10.1523/jneurosci.1026-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Reward Changes Salience in Human Vision via the Anterior Cingulate

Abstract: Reward-related mesolimbic dopamine steers animal behavior, creating automatic approach toward reward-associated objects and avoidance of objects unlikely to be beneficial. Theories of dopamine suggest that this reflects underlying biases in perception and attention, with reward enhancing the representation of reward-associated stimuli such that attention is more likely to be deployed to the location of these objects. Using measures of behavior and brain electricity in male and female humans, we demonstrate thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

84
621
13

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 539 publications
(718 citation statements)
references
References 49 publications
84
621
13
Order By: Relevance
“…More specifically, we demonstrated that stimuli associated with primary reward can involuntary orient spatial attention and that this modulation critically depends on the properties of the primary reward. These results are consistent with recent experiments testing the incentive salience hypothesis in humans, and showing involuntary attentional interference effects by rewardassociated cue (Anderson et al, 2011a(Anderson et al, , 2011bHickey & van Zoest, 2012;Hickey et al, 2010aHickey et al, , 2010bHickey et al, , 2011. Critically, our results also revealed that this attentional capture is independent of the stimuli's low-level perceptual characteristics.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…More specifically, we demonstrated that stimuli associated with primary reward can involuntary orient spatial attention and that this modulation critically depends on the properties of the primary reward. These results are consistent with recent experiments testing the incentive salience hypothesis in humans, and showing involuntary attentional interference effects by rewardassociated cue (Anderson et al, 2011a(Anderson et al, , 2011bHickey & van Zoest, 2012;Hickey et al, 2010aHickey et al, , 2010bHickey et al, , 2011. Critically, our results also revealed that this attentional capture is independent of the stimuli's low-level perceptual characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…This rapid effect of reward is consistent with Hickey et al (2010a)s electrophysiological findings showing that brain activity is influenced at early stages by the perception of reward-associated stimuli. Our findings suggest that this modulation of early brain activity could be translated in a similarly rapid modulation of involuntary attentional orienting which would influence behavior.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations